The pilot's wife : a novel - Shreve, Anita (Boston : Little, Brown, 1998)
Kathryn Lyon's life was peacefully routine, she had a good job and a happy marriage, so when she received the news that her pilot husband has died in a crash, her world was drastically changed. Even before his body is recovered the media discovers that her husband had a secret life, and Kathryn sets out to learn who her husband really was.
Wilson's Fiction
Pub Weekly
Booklist
Adult
Keywords: Man-woman relationships -- Fiction; Secrecy -- Fiction; Death -- Fiction; Man-woman relationship -- Fiction; Secrets -- Fiction; Death -- Fiction